Renaissance dan Pergeseran Epistemologi Barat: Analisis Kritis terhadap Paradigma Sains Bebas Nilai dan Krisis Etika Teknologi Modern: The Renaissance and the Shift in Western Epistemology: A Critical Analysis of Value- Free Science and Technological Ethics - Dinda Aulia Putri; Zakaria Husin Lubis (University of Darussalam Gontor, Indonesia, 2026)
Modern science has generated technological advancements with significant destructive potential, including nuclear weapons and genetic engineering, despite the normative expectation that scientific inquiry should be grounded in ethical values that uphold human dignity. This disjunction originates from an epistemological shift during the Renaissance, when elements of the Islamic intellectual tradition were selectively appropriated while their theological foundations were marginalized, resulting in a value-free scientific paradigm. This study examines this epistemological transformation, analyzes its implications for contemporary technology, and proposes a framework through the integration of maqāṣid al-Syarī‘ah and qawā‘id fiqhiyyah. It employs a qualitative library-based methodology with historical, comparative, and synthetic-prospective analyses. The findings indicate three key points. First, there is a substantive link between the Renaissance epistemological shift and the modern technological ethical crisis. Second, critiques of technological exploitation are not limited to Islamic thought but are also expressed by Western thinkers such as Jürgen Habermas; however, the Islamic framework provides a more systematic and hierarchical ethical model. Third, this framework demonstrates practical relevance, particularly in prohibiting nuclear weapons based on ḥifẓ al-nafs and the principle lā ḍarar wa lā ḍirār, as well as in classifying embryo selection as taḥsīniyyāt. This study argues that reintegrating revelatory values into science is essential to ensure that technological progress remains aligned with human dignity.